1998
DOI: 10.1046/j.1365-2036.1998.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cisapride on gastric tone and the perception of gastric distension

Abstract: Background: Delayed gastric emptying, impaired gastric accommodation to a meal and hypersensitivity to gastric distension have been implied in the pathophysiology of functional dyspepsia. Dyspeptic patients are often treated with the prokinetic drug cisapride. Aim: To assess the effects of cisapride on perception of gastric distension and gastric accommodation to a meal. Methods: Eighteen healthy volunteers underwent a gastric barostat study on two occasions, after pre‐treatment with placebo or cisapride 10 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
2
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 19 publications
(41 reference statements)
3
97
2
2
Order By: Relevance
“…Pretreatment with cisapride was shown to significantly enhance the accommodation to a meal in healthy subjects, suggesting potential benefit of 5-HT 4 receptor agonists in patients with impaired gastric accommodation. 78 More recently, a relaxatory effect on the proximal stomach was confirmed for the 5-HT 4 receptor agonist tegaserod. 79 We have shown that administration of sumatriptan, a 5-HT 1 receptor agonist, also relaxes the proximal stomach in healthy subjects 80 and, in acute studies, is able to restore the meal-induced relaxation in patients with impaired gastric accommodation and to increase the amount of calories ingested at maximum satiety in patients with early satiety.…”
Section: Fundus-relaxing Drugsmentioning
confidence: 93%
See 2 more Smart Citations
“…Pretreatment with cisapride was shown to significantly enhance the accommodation to a meal in healthy subjects, suggesting potential benefit of 5-HT 4 receptor agonists in patients with impaired gastric accommodation. 78 More recently, a relaxatory effect on the proximal stomach was confirmed for the 5-HT 4 receptor agonist tegaserod. 79 We have shown that administration of sumatriptan, a 5-HT 1 receptor agonist, also relaxes the proximal stomach in healthy subjects 80 and, in acute studies, is able to restore the meal-induced relaxation in patients with impaired gastric accommodation and to increase the amount of calories ingested at maximum satiety in patients with early satiety.…”
Section: Fundus-relaxing Drugsmentioning
confidence: 93%
“…88 However, the selective 5-HT 3 antagonists alosetron and ondansetron do not appear to have any significant effects on sensitivity to gastric distension in humans. 89,90 A recent study demonstrated reduction in dyspeptic symptoms in functional dyspepsia patients treated with alosetron. 91 The mechanism underlying this beneficial effect remains to be elucidated, but additional studies with alosetron are unlikely because this drug has been withdrawn due to side effects.…”
Section: Antinociceptive Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…29) Previous studies suggested that the activity of CTE and its main component, corydaline, may be related to the 5-HT 4 receptor because the 5-HT 4 receptor agonists cisapride and tegaserod are known to accelerate GE and small bowel transit and enhance gastric accommodation in humans. [32][33][34][35][36] Furthermore, corydaline has weak affinity for the 5-HT 1A , 5-HT 1B , and non-selective 5-HT 1 receptor subtypes (pK i Ͻ5; data not shown), thus excluding the 5-HT 1 receptors from the gastric-relaxing effect. Further study is necessary to clarify the mechanisms of action of corydaline.…”
Section: )mentioning
confidence: 99%
“…This could explain the variety of drugs which show a positive symptomatic response [1] , currently there is no FDA-approved drug for treatment of FD [3] . Despite the scant evidence, anti-secretory agents are frequently recommended in the treatment of patients with a predominant complaint of pain while prokinetic agents are frequently used for bloating and early satiety [4] . Patients' symptoms that are severe enough to disrupt daily activities will likely benefit from pharmacologic therapy.…”
Section: Introductionmentioning
confidence: 99%